Effect of emitter proprties on the conversion efficiency of silicon solar cells - Gorban, A.P.; Kostylyov, V.P.; Sachenko, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The effect of donor concentration distribution N(x) in the n⁺-emitter on the conversion efficiency h of silicon n⁺-p-p⁺ solar cells is studied theoretically. Shockley-Reed-Hall recombination in the emitter is taken into consideration together with band-to-band Auger recombination. The calculation is performed in the approximation when in the region with changing concentration a small part of generated electron-hole pairs recombines. It is shown that, in general, the correlation between h and p-n - junction depth is absent.